The Use of Pancasila Smart Book to Improve Basic Literacy of Indonesia Immigrant Workers Children in Malaysia - Armiani, Risma Ika Putri; Syam, Aldo Redho; Sumaryanti, Lilis; Chaniago, Zamawi (Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2025)
Students' early reading skills at the Sanggar Bimbingan (SB) in Hulu Langat, Malaysia, often present a challenge that impacts the effectiveness of the learning process. Many children of Indonesian migrant workers face difficulties in developing reading skills and have a limited understanding of Pancasila values. To address this issue, the Smart Book Pancasila was introduced as an innovative learning tool designed to create a more engaging and interactive learning environment.  This study explores how the Smart Book Pancasila helps improve early reading abilities and the comprehension of Pancasila values among students at SB Hulu Langat. Using a descriptive qualitative approach, data was collected through interviews, observations, and documentation. The primary informants included administrators, teachers, and students.  The findings indicate that the use of the Smart Book in Pancasila learning contributes positively to the improvement of students' reading skills. Using interactive visuals and engaging content helps students better understand reading material while also internalizing the values of Pancasila. Thus, the Smart Book Pancasila is an effective alternative strategy for early literacy development, particularly for children with limited access to formal education.